Enseñanza de la Fonética Inglesa a través de Jolly Phonics - Hualde-Ruiz, Ana Rosa (My University, 2015)
El presente proyecto de investigación tiene como finalidad conocer la educación bilingüe en España y conocer los métodos de enseñanza que trabajan la enseñanza del inglés y más concretamente, la lectura. Jolly Phonics es un método actual que trabaja una habilidad muy poco desarrollada en las aulas españolas, la pronunciación. Por medio del estudio de investigaciones realizadas en diferentes colegios, tanto en Reino Unido como fuera de él, donde el idioma materno no es el inglés, hemos querido oportuno mostrar los resultados obtenidos en dichos colegios, en los que se han conseguido avances asombrosos tanto en lectura como en escritura. El currículo español no muestra en sus objetivos específicos el conocimiento de la pronunciación inglesa, aunque para una real puesta en práctica es obligatorio su desarrollo, y una buena manera es el conocimiento de métodos reales como Jolly Phonics que enseña de manera divertida y entretenida, a la vez que fomenta el interés por la lectura y por la lengua extranjera.
The purpose of this reach work is to evaluate bilingual education in Spain, and to investigate the various teaching methods applied in developing English language learning, with special emphasis as Reading. Jolly Phonics is an actual and synthetic method which exercises a skill that is not very developed in Spanish classrooms in the teaching and learning of English, and that is pronunciation. Through the study and investigation of research in different schools, both in the UK and outside, where the mother tongue is not English, we find the results obtained in the schools indicate amazing advances in both reading and writing. The Spanish curriculum does not include any specific learning objectives with regard to the knowledge of English pronunciation. However, for the effective teaching and learning of English in Spain, the inclusion of pronunciation skills in the curriculum is necessary and obligatory. An effective method of teaching pronunciation is through an approach called Jolly Phonics. Jolly Phonics is a fun-centre approach teaching literacy through synthetic phonics. It teaches pronunciation in a fun and entertaining way, while at the same time promoting an interest in reading, and in English as a foreign language.
Keywords: Jolly Phonics; reading; métodos de aprendizaje; inglés; fonética; educación primaria; Grado en Maestro en Educación Primaria